Post-evaluation System In Construction Projects In Gaza Strip-palestine - Enshassi, Adnan Ali; Arain, Faisal; Rayyes, Yasmine El- (Penerbit Universiti Sains Malaysia, 2014)
A construction project can be described as successful when it is completed on time, within budget and according to specifications. Post-evaluation plays a major role in the construction industry when determining whether the project is a success or a failure. The objectives of this paper are as follows: to provide an overview of an organisation's interest in the post-evaluation system of the construction projects in the Gaza Strip, to identify and rank the most important factors used in the post-evaluation system for construction projects, to identify the obstacles of the post-evaluation system and to determine the factors that lead to a successful post-evaluation system. A structured questionnaire was adopted in this study; 40 questionnaires were distributed to international organisations that implemented construction projects in the Gaza Strip. The ordinal data were analysed by the relative important index method, which was used to rank the factors and the groups of the questionnaire and the nominal data were analysed by the relative frequency or percentage. The research findings revealed that international organisations in the Gaza Strip are concerned with the post-evaluation system of construction projects because postevaluation is required by all donors. Cost, time and quality are found to be the most important group factors for the post-evaluation system of construction projects. The factors that are used in the process of post-evaluation include the following: project efficiency, owner satisfaction, project effectiveness, safety, risks, change orders, resources, communication, procurement and the environment. Overloaded projects were found to be the largest obstacle to the process of post-evaluation. A lack of awareness about postevaluation will increase the risk of not complying with donor requirements, which affects potential future funding. Evaluator efficiency was found to be the most important factor leading to a successful post-evaluation system. This paper recommends that organisations consider other factors, such as safety and environmental impact. It is advisable to consider risk factors in the evaluation process because the Gaza Strip suffers from political and economic instability and to increase the evaluators' awareness concerning environmental and safety impacts in the evaluation process. The findings from this study would also be valuable for all construction professionals involved in the construction industry in general